Vivencia holística del estrés en profesionales de Enfermería. - Espinoza Guerrero, Marianela; Valverde Hidalgo, Sharon; Vindas Salas, Hellen (Nursing Journal in Costa Rica, 2011)
This article presents the results of developing a holistic program for the experience of stress in professiona l the Nurses. The participant population was a group of nurses working in the operating room of the Hotel La Catolica Hospital. Methodology: a phenomenological qualitative research. Program development group intervention was used, which was considered the group dynamics and the processes underlying psychological reality expressing the functional group. We determined an input profile under the assumptions of Betty Neuman and applied the five steps of the systematization, as recommended by Jara (2004). Results : Participants felt that nurses experience significant medium to stress factors such as self-confidence, expression of feelings, autonomy and problem-solving. Other issues that create stress are making decisions, irreversibility of actions, grooming, feeding and management of emotions. In the extra-personal environment, was awarded a maximum stress level of public safety, pollution and place of residence in the workplace, two people saw it as the greatest stress causes them and three others placed him at the intermediate level Conclusion: Nurses maintain high levels of stress factors related to the intrapersonal and interpersonal environment in which to work on strengthening the vital psychological characteristics was very important to find the relationship stress - illness. In addition, gender influences the creation of an environment that makes them unable to self-care, so that the field work that resulted in each of the members a comprehensive view on itself, which includes body, mind and spirit strengthen their mental health.